2020
DOI: 10.1002/hep.31184
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Acts Through Estrogen Receptor 2b to Regulate Hepatobiliary Fate During Vertebrate Development

Abstract: Background and Aims During liver development, bipotent progenitor cells differentiate into hepatocytes and biliary epithelial cells to ensure a functional liver required to maintain organismal homeostasis. The developmental cues controlling the differentiation of committed progenitors into these cell types, however, are incompletely understood. Here, we discover an essential role for estrogenic regulation in vertebrate liver development to affect hepatobiliary fate decisions. Approach and Results Exposure of z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The Hippo/ YAP pathway is crucial for liver size control; hyper-YAP1 activity in the liver stimulates hepatocyte and cholangiocyte specification, whereas loss of YAP1 decreases hepatocyte survival and impairs biliary duct morphogenesis (12). Notch signaling and esr2b are also involved in hepatocyte differentiation and bile duct formation (13,14). Numerous transcription factors govern cell fate choices.…”
mentioning
confidence: 99%
“…The Hippo/ YAP pathway is crucial for liver size control; hyper-YAP1 activity in the liver stimulates hepatocyte and cholangiocyte specification, whereas loss of YAP1 decreases hepatocyte survival and impairs biliary duct morphogenesis (12). Notch signaling and esr2b are also involved in hepatocyte differentiation and bile duct formation (13,14). Numerous transcription factors govern cell fate choices.…”
mentioning
confidence: 99%
“…Further analysis revealed that E2 signaling mediated by Esr2b operates upstream of essential distal transcription factors Irx3b and its target Irx1a (Wesselman et al, 2023). Taken together, Esr2b seems to regulate cell fate choice in multiple zebrafish tissues, as a similar phenotype was observed in liver tissue (Wesselman et al, 2023;Chaturantabut et al, 2020).…”
Section: Kidneymentioning
confidence: 79%
“…Gorelick and Halpern, 2011;Chaturantabut et al, 2020). esr2a is also expressed in neuromast cells, and esr2a and esr2b are expressed more in the intestine (Froehlicher et al, 2009;Menuet et al, 2002).…”
Section: Estrogen Signaling In Organogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Liver is known to be a target organ of oestradiol, which is crucial for liver regeneration after partial hepatectomy 33 and liver growth in mammalian neonates. 34 However, there are different opinions as to the mechanism of oestradiol promoting the liver growth. Uebi, T et al said that oestradiol controls the hepatocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%